Die voorkoms en funksie van dwelms in die Afrikaanse letterkunde - Van Rensburg, Elizabeth (University of the Free State, 2021)
Since the earliest recordings, drugs have been described as an influential part of social, psychological, technological and economic aspects of society. Herodotus is one example of an author who wrote about drug use as early as 440 B.C. All over the world, statistics show that drug use is increasing and expanding, and many changes to drug legislation are being considered. The primary goal of this study is to determine the incidence and literary function of drugs in the Afrikaans literature. Literature sociology holds that literature is a social occurrence and that literature and society reflects, as well as influence, each other. This approach enables the literature analyst to view literature as a mirror or as a reflection of reality. One of the benefits of this approach is that aspects of reality and literature, a portrayal of reality, can be compared against each other. By comparing these things, the success of certain literature devices, such as credibility, can be tested. For this study, literature sociology will be used to focus on one aspect of reality, namely drugs. A twofold analytical approach, using two main literature sociology thought streams, will be used to determine the literary function of drugs. Firstly, relevant drugs will be examined using a Marxist standpoint, meaning that the role, perspective and status of these drugs will be researched. Secondly, a critical reading approach, as suggested by Humanitarian literature sociologists, will be used to analyse texts. The focus of this analysis will be on drugs and its literary function. By comparing both viewpoints on drugs, the credibility of texts can be considered. Representative Afrikaans texts with drugs as the main or subtheme were selected to determine the incidence of drugs in Afrikaans literature. A few examples of these works include, among others, Vreemder as fiksie en ander konterfeitsels (1996) and Tweede natuur (2000) by Johann de Lange, Op soek na generaal Mannetjies Mentz (1998) by Christoffel Coetzee, Seks & drugs & boeremusiek (2000) by Koos Kombuis, In stede van die liefde (2005) by Etienne van Heerden, Donker liefde: my verhouding met heroïen (2007) by Anoux Venter, Noudat slapende honde (2008) and grond/Santekraam (2011)by Ronelda Kamfer and Tussen middernag en dagbreek (2012) by J.W. Bogaards. Firstly, a historic overview of drugs will be discussed. An archive of all relevant Afrikaans literature related to the topic will be listed and thereafter, an in-depth textual analysis will be made of four selected texts. Lastly, a conclusion will be drawn and possible suggestions for other research will be made. This reseach provides a new tool for examining literature from a certain perspective. This enables the researcher to link certain themes together, test the credibility of a text and examine literary elements from a new perspective.

Antieke tekste, soos Herodotus se The Histories, getuig van ’n eeueoue wisselwerking tussen dwelms, die literatuur en die samelewing. Alhoewel daar reeds navorsing bestaan oor dwelms as ŉ literêre tema, is die literêre funksie daarvan nog nie na wense in die Afrikaanse letterkunde bepaal nie. Die primêre doel van hierdie ondersoek is om vas te stel wat die voorkoms en funksie van dwelms in die Afrikaanse letterkunde is. Die literatuursosiologie verwys na die oortuiging dat die letterkunde ŉ sosiale verskynsel is en dat die letterkunde en die samelewing mekaar sistematies weerkaats, sowel as wedersyds beïnvloed. Die teorie stel literatuurwetenskaplikes in staat om die letterkunde as ŉ spieël van die werklikheid te beskou. Iets wat veral relevant is vir hierdie studie, is die feit dat literatuursosiologie gebruik kan word om ŉ teks se geloofwaardigheid, sowel as ander literêre funksies, ten opsigte van een aspek van die samelewing, naamlik dwelms, te toets. ŉ Tweeledige analise word gebruik om uiteindelik dwelms se funksie in die letterkunde te bepaal: eerstens word relevante dwelms in ŉ sosiale konteks nagevors en bespreek. Tweedens word tekste geanaliseer volgens die literêre bydrae wat dwelms tot die teks lewer. Op hierdie manier word ŉ dwelmblik op die letterkunde en die samelewing gewerp, om sodoende die twee teenpole direk teenoor mekaar te stel. Verteenwoordigende Afrikaanse tekste met dwelms as hoof- of subtema sal geselekteer en kortliks ontleed word om die voorkoms van dwelms te bepaal. Die literêre funksie van dwelms word aan die hand van vier tekste getoets. Die geselekteerde tekste sluit in Vreemder as fiksie en ander konterfeitsels (1996) en Tweede natuur (2000), deur Johann de Lange, Op soek na generaal Mannetjies Mentz (1998), deur Christoffel Coetzee, Seks & drugs & boeremusiek (2000), deur Koos Kombuis, In stede van die liefde (2005), deur Etienne van Heerden, Donker liefde: my verhouding met heroïen (2007), deur Anoux Venter, Noudat slapende honde (2008) en grond/Santekraam (2011), deur Ronelda Kamfer en Tussen middernag en dagbreek (2012), deur J.W. Bogaards. Hierdie navorsing bied ŉ argief van geselekteerde tekste met dwelms as hoof- of subtema in die Afrikaanse letterkunde. Die argief kan gebruik word om maatskaplike probleme, sowel as diskoers rakende dwelms te bestudeer. Verder kan die “dwelmlens” as invalshoek tot die letterkunde gebruik word in ander gevalle om die sukses van ŉ teks te toets.
Dissertation (M.A. (Afrikaans and Dutch, German and French))--University of the Free State, 2021
Keywords: Drugs and literature; Drugs in literature; Drugs of abuse -- Popular works; Drugs -- Afrikaans literature